Sustainable Agriculture Purchase Intention: The Moderating Role of Government Support in Farmers’ Adoption of Green Product, Pheromone Mating Disruption for Rice Cultivation in Karawang - Maulana Marman; Adi Nurmahdi (Indonesian Journal of Business Analytics, 2025)
Advancing sustainable agriculture requires farmer adoption of eco-friendly innovations such as pheromone mating disruption. This study analyzes how perceived benefit, perceived ease of use, and subjective norms shape farmers’ green purchase intention, with government support as a moderator. Survey data from 211 rice farmers in Karawang were examined using SEM-PLS (SmartPLS 4.0). All three factors significantly increased purchase intention. Government support amplified the perceived benefit effect, diminished the ease of use impact, and did not influence subjective norms. By integrating TAM and TPB, this research offers rare empirical evidence from Indonesia’s agricultural sector, highlighting the nuanced institutional role in the technology adoption of pheromone mating disruption. Findings inform targeted policy and marketing strategies for sustainable agriculture promotion.